Професійні вимоги та професійний імідж майбутнього іт-фахівця - Бедро, В. Ю. (ХНУРЕ, 2019)
The publication is devoted to the analysis of professional requirements and professional image of the future IT specialist. Graduates of university image, which need to be taken into account in the practical activities of forming the image of universities. Demonstrated on what the formation an effective professional image that promotes the competitiveness of a young specialist in the modem labor market, shows modem requirements of employers to IT specialists.